Youth Livelihoods in the Cellphone Era: Perspectives from Urban Africa. (10th January 2018) - Porter, Gina; Hampshire, Kate; de Lannoy, Ariane; Bango, Andisiwe; Munthali, Alister; Robson, Elsbeth; Tanle, Augustine; Abane, Albert; Owusu, Samuel
Abstract: Issues surrounding youth employment and unemployment are central to the next development decade. Understanding how youth use mobile phones as a means of communicating and exchanging information about employment and livelihoods is particularly important given the prominence of mobile phone use in young lives. This paper explores and reflects on youth phone usage in Ghana, Malawi and South Africa, drawing on mixed‐methods research with young people aged approximately 9–25 years, in 12 (high density) urban and peri‐urban sites. Comparative work across these sites offers evidence of both positive and negative impacts. The final section of the paper considers policy implications. © 2018 The Authors Journal of International Development Published by John Wiley & Sons Ltd.